Challenges with achieving and maintaining oral cholera vaccine coverage: insights from serial cross-sectional representative surveys in a cholera-endemic community in the Democratic Republic of the Congo - Oliver Cumming; Andrew S Azman; Espoir Bwenge Malembaka; Jackie Knee; Placide Okitayemba Welo; Aimé Cikomola; Aybüke Koyuncu; Patrick Musole Bugeme; Juan Dent; Chloe Hutchins; Hanmeng Xu; Karin Gallandat; et al. (BMJ Public Health)
Background We conducted three serial cross-sectional representative surveys after a mass cholera vaccination campaign in Uvira, Democratic Republic of the Congo to (1) estimate the vaccination coverage and explore heterogeneity by geographic and demographic factors; (2) examine barriers and facilitators of vaccine uptake and (3) describe the changes in coverage over time and predict future coverage.Methods We collected data on sociodemographics, self-reported vaccination status, population movement and knowledge, attitudes and behaviours related to killed oral cholera vaccines (kOCVs) in August 2021, April 2022 and April 2023, approximately 11, 19 and 30 months postvaccination. We compared the characteristics of participants by vaccination status and explored the potential role of population movement as a cause for low coverage. We used an exponential decay model to predict the proportion of the population vaccinated with ≥1 dose of kOCV over time based on age-specific coverage.Results We enrolled 8735 participants from 1433 households across all surveys. Coverage in survey 1 (August 2021) was 55% for ≥1 dose of kOCV (95% CI 51 to 60) and 23% for ≥2 doses (95% CI 20 to 27). Vaccine refusal was associated with a lack of confidence in the vaccine’s safety, and 29% of unvaccinated adults reported it was unlikely they would accept kOCVs if an additional mass vaccination campaign was conducted in their area. Coverage of ≥1 one dose of kOCV declined on average by 18% per year (95% credible interval 14 to 23) and was 39% (95% CI 36 to 43) by survey 3 (approx. 30 months after second dose campaign).Conclusions Our findings suggest that in settings like Uvira, efforts to strengthen vaccine confidence are needed to achieve higher campaign coverage, and vaccine coverage dilution may be reduced by more frequent and coordinated geographic vaccination efforts.